Pregnancy outcome in systemic lupus erythematosus patients: A case series (Indian Journal of Case Reports, 2018)
Systemic lupus erythematosus (SLE) is an autoimmune disorder that mainly affects reproductive age group women. Pregnancy may worsen SLE; especially, is associated with nephritis and SLE may lead to various pregnancy complications. Here, we present a series of eight known cases of pregnant women with SLE nephritis; of which 6 were booked and 2 cases were unbooked. Histological grading of renal involvement of the patients was done according to the World Health Organization classification/2004 classification of International Society of Nephrology/Renal Pathology Society. SLE activity in each patient was assessed using SLE disease activity index-2K. All cases were followed up to delivery and 12 months thereafter. It was found that the booked cases who conceived during disease remission had favorable outcomes, whereas, the unbooked cases had a disease flare during pregnancy leading to poor outcomes. Pregnancy should only be attempted after proper planning and disease remission in patients with SLE.